2014
DOI: 10.11622/smedj.2014056
|View full text |Cite
|
Sign up to set email alerts
|

Age- and gender-related differences in drug utilisation and adverse drug reaction patterns among patients in a coronary care unit

Abstract: INTRODUCTIONThis study aimed to examine age-and gender-related differences in the comorbidities, drug utilisation and adverse drug reaction (ADR) patterns of patients admitted to a coronary care unit (CCU). MeThODsThe present study was a retrospective cohort study. Two trained physicians independently reviewed the case records of CCU patients over a period of one year (Jan-Dec 2008). The demographic, clinical, and drug prescription data of the patients were analysed according to age group (18-59 years vs ≥ 60 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 38 publications
0
11
1
Order By: Relevance
“…Another retrospective study identified no significant gender-based differences in ADR patterns (p>0.05) in coronary care unit patients. But, this study found that the patients aged >60 years had a higher rate of ADRs (p=0.013) than patients aged 18-59 years (Kunnoor et al, 2014).…”
Section: Adverse Drug Reactions In Specific Populationcontrasting
confidence: 58%
“…Another retrospective study identified no significant gender-based differences in ADR patterns (p>0.05) in coronary care unit patients. But, this study found that the patients aged >60 years had a higher rate of ADRs (p=0.013) than patients aged 18-59 years (Kunnoor et al, 2014).…”
Section: Adverse Drug Reactions In Specific Populationcontrasting
confidence: 58%
“…found that ADRs are more common among females but they opined that further work is needed to elucidate the reason behind such differences. [ 20 ] Kunnoor et al [ 23 ] in their study, which was conducted on patients admitted to a coronary care unit found gender-related differences in the ADR patterns, although polypharmacy was more common in males but ADRs were 1.5- to 1.7-fold more common in females than males. Their explanation for these differences was different pharmacokinetic, pharmacodynamic, immunological, and hormonal factors in females as well as differences in the pattern of use of medications in them.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum number of studies were found in this category, even a systematic review has been done (Bachhav and Kshirsagar, 2015). These studies were hospital- (Mittal et al, 2014) or ward-or unit-oriented, for instance medical emergency (Dhamija et al, 2013;, CCU (Kunnoor et al, 2014), disease (eclampsia)-oriented (Kumar et al, 2014); although we found an interesting study that focused on one drug, pioglitazone . The late Prof. RR Chaudhary had asked us to conduct a drug utilization study to provide background data so that appropriate amendments regarding drug procurement and dispensing policies can be made (Singh et al, 2010) although we did not find recent studies conducted for this purpose.…”
Section: Rational Use Of Drugs Drug Utilization Studies and Prescripmentioning
confidence: 84%